Teacher education and gender diversity in higher education: an analysis of curricular matrices (Research, Society and Development, 2021)
This article intends to demystify some classifications that involve gender diversity in higher education. For this, the curricular matrices of the degree courses in Pedagogy, Mathematics, Biology, History, Geography, Physical Education, Physics, Literature and Chemistry at the Federal University of Jataí-Goiás were analyzed. We tried to identify whether these courses have included themes in their disciplines that provoke reflection on gender diversity. Thus, the purpose of this research is to reveal how gender diversity has been guided in the university courses mentioned above; still, the clarification of concepts existing in the LGBTTT classes is being covered, which are: Lesbians, Gays, Bisexuals, Transvestites, Transsexuals and Transgender. To do so, we base ourselves on the discussions of Tomaz Tadeu da Silva (1999), Jimena Furlani (2011) and Guacira Lopes Louro (2010), reference authors on the theme of diversity. This research is classified as bibliographic and documental, qualitative in nature, with secondary data collection through the syllabuses of the disciplines and pedagogical projects of the courses. The intention is to promote a less homo/bi/transphobic view, which intensify the problematization of the theme in Higher Education. Through this conceptual study, it is possible for students to approach the subject in a multidisciplinary way and deal with diversity, thus becoming individuals who understand the world in its multiple cultural diversities.